Migrants’ access to health: exploring the migrants’ interface with a mission and a state hospital on maternal health care provision in a Zimbabwean borderland - Vumai, Bothwell (My University, 2020)
Zimbabwe has in the past been one of the major migrants-receiving countries in the region and boasting a vibrant health delivery system till the late 1990s. From the year 2000 upwards, the standards within the Zimbabwean Health Delivery System grossly deteriorated due to a plethora of issues relating to a prolonged socio-economic and political crisis in the country which led to massive brain drain of qualified medical professionals, shortage of drugs, dilapidated infrastructure among others thereby making the health delivery system one of the poorest in the world (Zakeyo, 2015; Banda, 2015; Zakeyo and Lange, 2015; Munodawafa et al., 2017). Current evidence shows that Zimbabwe has a maternal mortality rate of 614/100 000, neo natal mortality rate of 26/1000 and child mortality rate of 75/1000 (Munodawafa et al., 2017; ZIMFACT, 2018), making it one with the highest maternal and neo-natal mortality rates in the region. Despite all this, Zimbabwean health care facilities continue to provide public and maternal health care services to refugee women and migrant women from Mozambique. Informed by the access to health and the maternal health delivery frameworks, the research thus seeks to unravel and explore the migrants and refugees` interface with a mission and a state hospital on maternal healthcare provision at a mission and a state-run hospital in Chipinge. It also seeks to explore how policies, legislative and institutional frameworks guiding mission and state-run hospitals shapes and impacts on the experiences of these Mozambican migrant women and refugee women in accessing maternal health care in a Zimbabwean borderland. The study identifies Mt Selinda mission hospital and Chipinge District hospital (both in Chipinge and close to the border between Zimbabwe and Mozambique) as the case studies. Qualitative methodology was employed in the research process. Research participants were recruited through a non-probability sampling technique. Purposive sampling and snowballing were utilized in the selection of participants. The target populations of the study were Mozambican migrant women and refugee women seeking maternal health care in Chipinge health facilities, maternal health care providers and hospital administrators of the institutions understudy. Data was collected using the semi-structured interviews, in-depth interviews, extensive literature review and observations as the major research instruments. Data analysis was done through the thematic content analysis procedure. This research report carries a significant scholarly and empirical function of informing the government, related line ministries and the region on the need for well-informed health programmatic responses to migration and access to public healthcare and maternal health care. It also serves to provide recommendations for improving accessibility and provision of maternal health services to migrant and refugee women as well as improving their health and wellbeing in this borderland community
A thesis submitted to the African Centre for Migration and Society, School of Social Sciences at the University of the Witwatersrand in partial fulfilment of the requirements for the award of Master of Arts in the field of Migration and Displacement, 2020